2021
DOI: 10.1111/liv.15128
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma after treatment cessation in non‐cirrhotic HBeAg‐negative chronic hepatitis B: A multicentre cohort study

Abstract: Background and Aims: Scarce data exist on the effect of nucleos(t)ide analogue (NA) discontinuation on hepatocellular carcinoma (HCC) risk in HBeAg-negative chronic hepatitis B (CHBe−). Therefore, we assessed whether HCC risk is increased in noncirrhotic CHBe− patients who discontinue compared to those remaining on NAs. Methods: This cohort study included 650 consecutive non-cirrhotic Caucasian or Asian patients with CHBe− without a history of HCC who discontinued NAs after a median of 5 or 3 years (cases, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…There have been several case reports and small studies describing severe hepatic flares or acute exacerbation of hepatitis B after NA cessation, which are sometimes fatal (11)(12)(13)(14)(15). Thus far, there has been 1 large cohort study reporting off-therapy incidence rates of hepatic decompensation and hepatocellular carcinoma among Asian, pretherapy HBeAg-negative patients who discontinued NAs as per the Asian Pacific Association for the Study of the Liver guidelines (16,17). While most studies have reported a higher incidence of liver-related complications among chronic hepatitis B (CHB) patients with cirrhosis, liver failure associated with HBV reactivation after NA withdrawal among patients without documented cirrhosis has also been reported (18).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several case reports and small studies describing severe hepatic flares or acute exacerbation of hepatitis B after NA cessation, which are sometimes fatal (11)(12)(13)(14)(15). Thus far, there has been 1 large cohort study reporting off-therapy incidence rates of hepatic decompensation and hepatocellular carcinoma among Asian, pretherapy HBeAg-negative patients who discontinued NAs as per the Asian Pacific Association for the Study of the Liver guidelines (16,17). While most studies have reported a higher incidence of liver-related complications among chronic hepatitis B (CHB) patients with cirrhosis, liver failure associated with HBV reactivation after NA withdrawal among patients without documented cirrhosis has also been reported (18).…”
Section: Introductionmentioning
confidence: 99%
“…1 ). [12] , [13] , [14] , [17] , [18] , [19] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] One of the studies involved two distinct cohorts, of which one consisted exclusively of individuals with prior severe acute exacerbation and the other consisted of patients who had never experienced such an event. 31 Therefore, 50 studies with 51 cohorts were included in the meta-research analysis.…”
Section: Resultsmentioning
confidence: 99%
“…3 presents the reported proportions of patients who experienced hepatitis flare-related death or liver transplantation according to follow-up duration, inclusion of individuals with cirrhosis, and number of enrolled patients. Most of the studies (30 of 37 studies, 81.08%) with a sample size <500 reported zero events, 13 , 14 , [30] , [31] , [32] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , 46 , [48] , [49] , [50] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , 72 and two of the five studies with a sample size of 500–1,000 also reported zero events ( Fig. S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy has also been accepted for patients with liver cirrhosis by APASL, 4,17,18,45 but still not by AASLD and EASL guidelines 5,6 . Of note, large studies have demonstrated that the incidence of HCC after cessation of effective finite Nuc therapy in HBeAg‐negative patients with CHB or cirrhosis are not higher than those who continued long‐term Nuc therapy 45–47 . With these favorable results, there seems no contraindication for finite Nuc therapy in patients with cirrhosis if proper off‐Nuc monitoring is guaranteed.…”
Section: Conclusion and Perspectivementioning
confidence: 99%